2014
DOI: 10.1371/journal.pone.0092710
|View full text |Cite|
|
Sign up to set email alerts
|

Allergic Airway Inflammation by Nasal Inoculation of Particulate Matter (PM2.5) in NC/Nga Mice

Abstract: To evaluate the effect of airborne particulate matter 2.5 (PM2.5) in winter on airway inflammation, water-soluble supernatant (Sup) and water-insoluble precipitate (Pre) in PM2.5 were inoculated in NC/Nga mice with high sensitivity to mite allergens. Sup with aluminum oxide was injected intraperitoneally for sensitization. Five days later, Sup, Pre or both Sup and Pre were inoculated via the nasal route five times for more sensitization and a challenge inoculation on the 11th day in NC/Nga mice. On the 12th da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
58
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(67 citation statements)
references
References 41 publications
7
58
2
Order By: Relevance
“…Reactive inflammation in lesions in which β2-microglobulin amyloid was deposited was associated with a marked infiltration of activated macrophages expressing cytokines, such as interleukin-1, tumor necrosis factor-alpha, and transforming growth factor-beta [14]. Only animal study also showed that after oropharyngeal aspiration of PM 2.5 , robust production of IL-1 by leukocytes in the lung tissue was noted [15, 16]. Brucker et al showed that PM 2.5 was also associated with higher inflammatory markers, including IL-1β in taxi drivers with occupational exposure to air pollution [17].…”
Section: Discussionmentioning
confidence: 99%
“…Reactive inflammation in lesions in which β2-microglobulin amyloid was deposited was associated with a marked infiltration of activated macrophages expressing cytokines, such as interleukin-1, tumor necrosis factor-alpha, and transforming growth factor-beta [14]. Only animal study also showed that after oropharyngeal aspiration of PM 2.5 , robust production of IL-1 by leukocytes in the lung tissue was noted [15, 16]. Brucker et al showed that PM 2.5 was also associated with higher inflammatory markers, including IL-1β in taxi drivers with occupational exposure to air pollution [17].…”
Section: Discussionmentioning
confidence: 99%
“…We are the first to demonstrate that pure PM2.5 collected in Yokohama City using the cyclone system evoked allergic airway inflammation in mice. We previously reported that PM2.5 collected using a high volume air sampler and eluted from filters induced allergic airway inflammation, as represented by an increase in AHR, the number of eosinophils in BALF, and the expression of cytokines such as IL‐4, IL‐13, and IL‐1β (Ogino et al, ). In the present study, the expression of IL‐5 and IL‐22 was up‐regulated, whereas that of IL‐4, IL‐13, and IL‐1β was not.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, PM 2.5 accumulates toxic heavy metals, acid oxides, organic pollutants, bacteria and viruses in the air, PM 2.5 can also remain in the air for a long time and be deposited in the lungs through inhalation, so it is a major threat to human health (2,3). Numerous previous studies have suggested that PM 2.5 can stimulate the production of reactive oxygen species (ROS) and certain inflammatory mediators, resulting in changes to vascular permeability, airway constriction and tissue injury (4)(5)(6). The majority of previous studies investigating PM 2.5 have histopathologically examined lung sections (7,8).…”
Section: Introductionmentioning
confidence: 99%